Advancements in Dalpiciclib for the Treatment of Breast Cancer Patients: A Review - Chen Z; Xie P; Chen Q; Ouyang J (Breast Cancer: Targets and Therapy)
Zhimin Chen,1,2 Pengjun Xie,1,2 Qihai Chen,1,2 Jie Ouyang1– 3 1The First Clinical Medical College of Guangdong Medical University, Zhanjiang, People’s Republic of China; 2Department of Breast Surgery, Dongguan Dungwah Hospital, Dongguan, People’s Republic of China; 3Dongguan Key Laboratory of Breast Cancer Prevention and Treatment, Dongguan, People’s Republic of ChinaCorrespondence: Jie Ouyang, Email kitty865@163.comAbstract: Combining cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6 inhibitors) with cyclin-dependent proteins can reduce the formation of cyclin D-CDK4/6 complexes, resulting in the inactivation of downstream genes and suppression of cell proliferation. Previous research on the use of CDK4/6 inhibitors in combination with endocrine therapies and anti-HER2 targeting agents across various subtypes and stages of breast cancer has shown promising outcomes in patient prognoses and tolerable drugs toxicities. For the present, the CDK4/6 inhibitors that have been widely used for the treatment of breast cancer are palbociclib, abemaciclib and ribociclib. Dalpiciclib (SHR6390), a novel and selective CDK4/6 inhibitor developed in China, has been approved by the National Medical Products Administration. The researches about dalpiciclib with different anti-tumor drugs are ongoing to explore the efficacy and the best strategies to use dalpiciclib. This review provides an overview of the research progress on dalpiciclib across different breast cancer subtypes with various anti-tumor drugs in different treatment opportunities.Keywords: breast cancer, dalpiciclib, CDK4/6 inhibitors, cyclin D